2008
DOI: 10.2460/ajvr.69.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical ophthalmic application of cidofovir on experimentally induced primary ocular feline herpesvirus-1 infection in cats

Abstract: Twice-daily application of 0.5% cidofovir solution in both eyes significantly decreased the amount of viral shedding and the severity of clinical disease in cats with experimentally induced ocular FHV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 21 publications
3
66
0
3
Order By: Relevance
“…The efficacy of these drugs is not supported by the published data, although topical application of cidofovir in FeHV-1 primary ocular infection has shown promising results (FONTENELLE et al, 2008). In vitro studies have shown that FeHV-1 is susceptible to feline IFN or recombinant human Ciência Rural, v.45, n.6, jun, 2015.…”
Section: Treatmentmentioning
confidence: 58%
See 1 more Smart Citation
“…The efficacy of these drugs is not supported by the published data, although topical application of cidofovir in FeHV-1 primary ocular infection has shown promising results (FONTENELLE et al, 2008). In vitro studies have shown that FeHV-1 is susceptible to feline IFN or recombinant human Ciência Rural, v.45, n.6, jun, 2015.…”
Section: Treatmentmentioning
confidence: 58%
“…Nasal discharge may be reduced by using saline solutions and topical ointments. Mucolytic drugs, including bromhexine, may also be useful (GASKELL et al, 2007;FONTENELLE et al, 2008;MALIK et al, 2009).…”
Section: Treatmentmentioning
confidence: 99%
“…Overall, and importantly, the results in the whole corneal explant model appear to match what has been observed in vivo with these two antivirals. Indeed, cidofovir treatment at a 12 h interval and a dose of~16 µM was quite effective at inhibiting FHV-1 replication in the corneal explant model, similarly to its antiviral effects in vivo as assessed by a reduction in viral titres in ocular swabs of experimentally infected cats (Fontenelle et al, 2008). When looking at acyclovir, much higher concentrations,~180 µM, were needed to efficiently inhibit FHV-1 replication at a similar treatment interval in the feline corneal explant model and a much larger standard deviation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many antivirals require frequent topical application and most lack well-controlled in vivo studies to justify their clinical use (Gould, 2011). Cidofovir is one of the few nucleosides analogues that have been tested in cats under well-controlled experimental conditions and showed a 33 % reduction in FHV-1 viral titres in FHV-1-infected, cidofovir-treated cats compared to FHV-1-infected, untreated control cats (Fontenelle et al, 2008). Another nucleoside analogue frequently used to inhibit alphaherpesvirus replication is acyclovir.…”
Section: Introductionmentioning
confidence: 99%
“…190 The activity of cidofovir against EHV-1 was recently confirmed (and extended to PMEDAP), 191 and both cidofovir and PMEDAP were also found active against feline herpesvirus type 1 (FHV-1). 192,193 Of direct veterinary importance, Fontenelle et al 194 found that topical ophthalmic application of cidofovir significantly decreased the amount of viral shedding and the severity of clinical disease in cats with experimentally induced ocular FHV-1 infection. Tempesta et al [195][196][197] recently demonstrated that cidofovir is effective against caprine herpesvirus type 1 (CpHV-1)-induced genital lesions in goats.…”
Section: D8 Therapeutic Potential Of Cidofovir and Anps For Veterinamentioning
confidence: 99%